Impacto do tratamento antihelmíntico de cães na contaminação de vias públicas por agentes de Larva Migrans - Ramires, Lívia Magosso (2014)
The geohelminthoses are important diseases that infect human beings. These diseases are caused by parasites that harbor the man as definitive host. In addition, dogs and cat may be responsible by environmental contamination by agents with zoonotic potential, particularly Toxocara spp. and Ancylostoma spp. These parasites may cause the visceral/ocular and cutaneous larva migrans syndromes, respectively. The drastic increase of people who raise dogs and cats with no parasitic control and the free access of these animals to sidewalks/recreative public areas are important factors for soil contamination by larva migrans agents. The aim of the study was to evaluate the impact of deworming in dogs on the environmental contamination of sidewalks/streets and public parks caused by larva migrans (LM) agents (Toxocara spp. and/or Ancylostoma spp.). The study was carried out in a disadvantaged social area of Presidente Prudente, São Paulo, Brazil. A survey was applied to 138 dog owners, who received a plastic bag (Cata-Caca MSD) to collect a stool sample of their animals (n=200). Further, stool samples of dogs observed in sidewalks/streets (440) and two parks (n=63) were also collected. The samples were analyzed by the Gordon and Whitlock technique, to evaluate the egg count of LM agents. The positive dogs (at least one egg per gram (epg)= 100) were submitted to an anthelminthic treatment (Fembendazole, Panacur® 10%). The egg count was verified in 32.5% (65/200) of the dogs, in 45.25% (62/137) of the stool samples found on the sidewalks/streets and in 3.7% (14/37) of the samples collected in the parks. Following 30 days after deworming, the effectiveness of treatment for Ancylostoma spp. and for Toxocara spp. was 95.8% and 96.6%, respectively. In addition, it was observed a highly significantly reduction in the contamination of environment by LM agents (sidewalks/streets and parks) after treatment of the dogs (p<0.0001). This findings were also observed in the sidewalks/streets, in which there was a significant reduction (p<0.0128) in the count mean of Ancylostoma spp. epg. However, the same phenomenon was not observed taking into account the contamination of the parks. The high infection of dogs with Ancylostoma spp. and/or Toxocara spp. observed in this study indicates that LM agents represent a risk for both the health of dogs and their owners. The deworming of domiciliated dogs should be considered an important and significant impact for the reduction of environmental contamination of public places by LM agents.